Large scale and interactive fluid simulation and rendering using the smoothed particle hydrodynamics technique on GPU - BRITO, Caio José dos Santos (2018)
Fluid simulation using meshless methods has increasingly become a robust way to solve mechanics problems that require dealing with large deformations and has become very popular in many applications such as naval engineering, mechanical engineering, movies, and games. One of the main methods is the Smoothed Particle Hydrodynamics (SPH) which has the challenge of simulating fluid with different behaviors (multiphase, viscoelastic, viscoplastic, turbulent), and to render high visual quality results in real time. The main goals of this work are to investigate the following subjects: (a) the simulation of weakly compressible fluids using SPH for different behaviors, (b) the simulation of fluids in large scale and at interactive frame rates and (c) the rendering of fluids with balance between performance and visual quality. The implemented tool can simulate multiphase flow and viscoelastic fluids up to 1 million particles on GPU in interactive rates of 15 fps for 100k particles and 2 fps for 1M particles. Also, two rendering approaches were proposed: the first based on local illumination for multiphase fluids in real time and, to accomplish a more realistic result, an interactive solution based on Ray Tracing was proposed.